Smart Arms Detection System Using YOLO Algorithm and OpenCV Libraries - Khalaf, Rayan; Akbulut, Yaman (My University, 2021)
The continuous development that the world is on must be pursued into human services, among these services provided by the modern world are the ability to detect faces, controlling and monitoring crowded places, the roads, auto-drive cars, and other smart systems that we can see through our daily life, these systems are known as object detection systems. This branch is getting development continuously and it gets big attention and support from international institutes, military institutions, and security companies. Object detection is a big branch and is used in many industries like medical, food production, plastic industries, controlling and monitoring roads, and more. In this paper we will explain information about object detection, its types, the YOLO algorithm, and a small idea that we made for controlling and monitoring arms showed by monitoring cameras or images that contain arms, we made it using the YOLO algorithm with the help of OpenCV and python libraries.
Keywords: Monitoring; object detection; digital; YOLO; arms detection